Produksi Biodiesel Dari Minyak Sawit Off Grade Menggunakan Katalis Na2O/Fe3O4 Pada Tahap Transesterifikasi - Widya Yoesepha; Zuchra Helwani; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Palm oil off grade is one of feedstock biodiesel from preparation of over done and decomposed palm oil. This palm oil off grade have >5% free fatty acid composition, therefore need two process to produce biodiesel that is esterification dan transesterification. The purpose of this research is to produce heterogen basic catalyst from iron powder impregnation with Na2O and study the effect of condition process variation. The variation of transesterification process is temperature (50oC, 60oC and 70oC), mole ratio of oil : methanol (1:6, 1:8 and 1:10) and catalyst concentration (1%-wt, 2%-wt and 3%-wt) as long as 3 hours. The result of this research was processed with Response Surface Methodology (RSM) and the number of steps was determined by Central Composite Design (CCD). The highest yield of biodiesel is 79,52% at temperature60oC, mole ratio oil : methanol 1:8 and catalyst concentration 2%-wt. The result showed that the catalyst concentration influencing the yield of biodiesel.Keywords: biodiesel, heterogen catalyst, palm oil off grade, response surface methodology, transesterification